Strontium titanate: From symmetry changes to functionality. Issue 1 (22nd September 2016) - Stöcker, Hartmut; Hanzig, Juliane; Zschornak, Matthias; Mehner, Erik; Jachalke, Sven; Richter, Carsten; Hanzig, Florian; Meutzner, Falk; Leisegang, Tilmann; Meyer, Dirk C.
Abstract : Pure strontium titanate exhibits a cubic perovskite‐type structure, but many approaches to break this high degree of symmetry are accessible. Since oxygen vacancies are the most prominent and most mobile defect species in strontium titanate, they play a crucial role also for structural changes due to external influences. Possible functionalities range from tuning of permittivity and conductivity to field‐induced structure changes, which lead to applications as solid‐state battery or switchable pyroelectric. Abstract : Pure strontium titanate exhibits a cubic perovskite‐type structure at room temperature, but many approaches to break this high degree of symmetry are accessible. The present review summarizes some possible methods by discussing the effects of stoichiometry variation, ion implantation, temperature treatment and external electric fields. Since oxygen vacancies are the most prominent and most mobile defect species in strontium titanate, they play a crucial role also for structural changes due to external influences. Possible functionalities range from tuning of permittivity, band gap and conductivity to field‐induced structure changes, which lead to applications as solid‐state battery or switchable pyroelectric.